This war ain't over : fighting the Civil War in New Deal America - Silber, Nina (University of North Carolina Press, 2018)
"The New Deal era witnessed a surprising surge in popular engagement with the history and memory of the Civil War era. From the omnipresent book and film 'Gone with the Wind' and the scores of popular theater productions to Aaron Copeland's 'A Lincoln Portrait, ' it was hard to miss America's fascination with the war in the 1930s and 1940s. Nina Silber ... examines the often conflicting and politically contentious ways in which Americans remembered the Civil War era during the years of the Depression, the New Deal, and World War II. In doing so, she reveals how the debates and events of that earlier period resonated so profoundly with New Deal rhetoric about state power, emerging civil rights activism, labor organizing and trade unionism, and popular culture in wartime"--